Methods in microbiology (Academic Press, 2007)
The second edition of Yeast Gene Analysis represents a major reworking of the original edition, with many completely new chapters and major revisions to all previous chapters. Originally published shortly after completion of the yeast genome sequence, the new edition covers many of the major genome-wide strategies that have been developed since then such as microarray analysis of transcription, synthetic gene array studies, protein microarrays and chemical genetic approaches. It represents a valuable resource for any research laboratory using budding yeast as their experimental system in which to identify new yeast gene functions. The chapters are written in a readable style with useful background information, technical tips and specific experimental protocols included as appropriate, enabling both the novice and the experienced yeast researcher to adopt new procedures with confidence